A Comparative Study On The Effect Of Chemical Additives On Clinker Grinding - Md Zan, Siti Rohaidah (Universiti Sains Malaysia, 2022)
The aim of the present research work is to improve the clinker performance by using a laboratory-scale ball mill to generate a high-quality mineral binder in terms of particle size, particle shape, and crystallization of particle. The experiment has been carried out in dry conditions, with around 1 kg of cement clinker sample measured using a measuring cylinder was ground with 20 kg of the steel ball. Characterization was done to the feed samples by X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). The grinding process were run without and with the addition of Triethanolamine (TEA) and two industrial grinding additives, MA. G. A/C379 and MA. G. A/C188 were employed in this experiment with dosages 0.05, 0.25, 0.50 and 1.00 wt.%. It was found that the addition of grinding aids with varied amounts of grinding aids has no significant influence on generating fine-size cement powder, according to the graph of particle size distribution. Furthermore, the particles formed are elongated, cubic, angular, rhombus, flaky, and irregular grains shape and it has been demonstrated that there is no significant difference because the grain shape achieved before and after grinding is nearly identical. The particle crystallinity of the ground product is also not noticeably changed. To summarise, it was found that the optimum grinding additives that can be used are MA. G. A/C379and MA. G. A/C188.